2001
DOI: 10.1111/j.1365-2621.2001.tb11346.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and Stability of (E, Z)‐2, 6‐Nonadienal, the Major Flavor Volatile of Cucumbers

Abstract: Factors affecting the production and stability of (E, Z)-2, 6-nonadienal (NDE) from pickling cucumbers were examined. Production capability was rapidly destroyed in tissues exposed to freezing, fermentation or processing conditions. Lower concentrations were produced by exocarp tissues than mesocarp or endocarp tissues, which probably accounted for an almost linear relationship between fruit size and NDE production. NDE production was reduced by acidification, enhanced by linolenic acid, and unaffected by othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…Of the 59 VOCs identified in cucumber, 19 had been reported previously, namely: acetaldehyde, propanal, hexanal, (E)-2-hexenal, (E)-2-heptanal, (E)-2-octenal, nonanal, (Z)-6-nonenal, decanal, (E)-2-nonenal, (Z,Z)-3,6-nonadienal, (E,Z)-2,6-nonadienal, (E,E)-2,4-decadienal, tetradecanal, 1-nonanol, (Z)-6-nonenol, (E)-2-nonenol, (E,Z)-3,6-nonadienol, and (E,Z)-2,6-nonadienol (Kemp et al, 1974;Schieberle et al, 1990;Buescher and Buescher, 2001;Palma-Harris et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 59 VOCs identified in cucumber, 19 had been reported previously, namely: acetaldehyde, propanal, hexanal, (E)-2-hexenal, (E)-2-heptanal, (E)-2-octenal, nonanal, (Z)-6-nonenal, decanal, (E)-2-nonenal, (Z,Z)-3,6-nonadienal, (E,Z)-2,6-nonadienal, (E,E)-2,4-decadienal, tetradecanal, 1-nonanol, (Z)-6-nonenol, (E)-2-nonenol, (E,Z)-3,6-nonadienol, and (E,Z)-2,6-nonadienol (Kemp et al, 1974;Schieberle et al, 1990;Buescher and Buescher, 2001;Palma-Harris et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is believed that the unsaturated aldehydes (E,Z)-2,6-nonadienal and (E)-2-nonenal are the most important VOCs in cucumber, since they are the most abundant VOCs (Kemp et al, 1974;Buescher and Buescher, 2001;Palma-Harris et al, 2001). (E,Z)-2,6-Nonadienal is known as the "cucumber aldehyde" due to its unique odour and relatively high abundance in cucumber (Schieberle et al, 1990).…”
mentioning
confidence: 99%
“…Therefore, chelation of zinc as well as other metals may have contributed to hindering NDEA and NEA degradation. EDTA, which is also an effective metal chelator, was unable to protect against degradation of NDEA and NEA in cucumber juice (Buescher & Buescher, 2001), but it is known to be less effective in complexing with Zn to inhibit ADH than PTL (Dickinson & Berrieman, 1977;Suzuki, 1966).…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of NDEA, would be beneficial for manufacturing products with natural cucumber flavor; however, NDEA and NEA are highly unstable in cucumber juice (Buescher & Buescher, 2001). NDEA stability was reported to be improved by acidification to low pH and especially by removal from acidified homogenates by distillation (Buescher & Buescher, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Isolation and identification of volatile components from blended cucumber tissue has shown that (E,Z)-nona-2,6-dienal and (E)-non-2-enal are the major components present. Most of the studies on flavor of cucumber have been done on blended cucumbers and are limited to the identification of aldehydes [2,3]. In this paper, we propose to characterize the whole volatile emission of pieces of cucumbers of five different tropical cultivars using SPME collection and gas chromatography/mass spectrometry (GC/MS) detection.…”
mentioning
confidence: 99%